Manajemen Pembinaan Anak Didik Pemasyarakatan Studi Kasus LPKA Kelas II Jakarta - Asri Rima Jiwantari; Mukhneri Mukhtar; Siti Zulaikha (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This This research aims to give a description and information about developmentmanagement in LPKA Kelas II Jakarta. This research uses qualititave approach withcase study models. Data were collected through observations, interviews, anddocumentation study that have been done in LPKA Kelas II Jakarta. The result ofresearch shows 1) Planning in child development is not works well, because there is nofunding for the development program from the government. Thus, causing LPKA work inagreement with another social institute 2) in organizing two functions of the institute,Lapas Class II A Salemba also exceed as Lapas for children and adults. 3) In leadershiprole, chief of LPKA coordinates another social institute for helping in execute childrendevelopment programs. 4) Each of development programs supervise by all members suchas staff, middle functionary, and high functionary. They are very responsible formonitoring toward daily development programs. In reporting, LPKA use online systemand manual reporting system.